PERAWATAN TEKNIK AKUPUNKTUR UNTUK PERCEPATAN PENYEMBUHAN LUKA POST PARTUM POST SECTIO CESAREA - Siska Suci Ginting; Lisa Putri Damanik; Isyos Sari Sembiring; Kamelia Sinaga; Monica Magdalena; Indah Falina (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2021)
Delivery by caesarean section can indeed facilitate the delivery process so that many pregnant women prefer to choose this route even though they can actually give birth normally. But in fact, the mortality rate by caesarean section is 40-80 per 100,000 live births. This figure has a 25x greater risk compared to vaginal delivery. The purpose of this service activity is focused on post partum patients with sectio caesarea who often experience disturbances such as frequent numbness, spinal pain, or abdominal pain. The problem is that there is no treatment method for post sectio caesarea postpartum patients so it is necessary to do community service with the aim of knowing the benefits of home care, namely acupuncture in post sectio caesaria post partum patients to accelerate the acceleration of post sectio caesarea wound healing. Respondents in this study consisted of two groups, namely the group that was given acupuncture treatment as many as 16 respondents and the control group without treatment as many as 15 respondents. The method used to analyze the data using the Mann-Whitney test. Wound healing variables were assessed based on the REEDA scale. Acupuncture was carried out for 3 consecutive days to determine the acceleration of post partum wound healing. The results of the analysis are P-Value = 0.001 <sig 0.05, which means that there is an effect of using home care with acupuncture techniques on the acceleration of the post partum wound healing process post sectio caesarea.